Implementation of a Web-based Cash Information System in The RT.010/08 Area of Ragunan, South Jakarta - S Sutisna; R Rasiban; Tri Wahyudi; Imam Muftadi; Muhammad Ilham Fadillah; Kurniawan Setyo Nugroho; Rudi Tri Jaya (IJISTECH (International Journal of Information System and Technology), 2022)
The Ragunan area specifically RT 010 RW 08 is an area that currently really needs a population administration information system that can perform data processing related to the process of providing information about the Ragunan area, specifically in RT 010 RW 08, such as registration of population data, family, date of birth, print out residents' correspondence, report on cash information from residents and report on residents' complaints to the head of the RT. In the data processing that is currently running, God is still recorded in the ledger. In services and public information, which is currently still done manually, and also all data is recorded in a ledger for making ktp (identity card) and also kk (family card) which must first look for data in the main population book. The obstacles faced in this process are activities that take time and the risk of data recording errors. This can be overcome by building a new system that is more effective and efficient, namely a web-based Information System using the MySql database.